ADVANCING ENGLISH FOR HANDLING COMPLAINTS: INTEGRATING TEACHING FACTORY AND CLASSROOM APPROACHES AT POLITEKNIK ELBAJO COMMODUS - Jufidah, Jufidah Jufidah; Wellalangi, Maria Beatrix Rahinart (Jurnal Pendidikan Bahasa Inggris Proficiency, 2026)
ABSTRACT Effective customer complaint handling in English is a critical skill in the maritime and tourism industries, particularly in destinations like Labuan Bajo, which contribute up to 5% to Indonesia’s national GDP. This study examines the effectiveness of integrating the teaching factory model at Senja Eatery with traditional classroom learning to enhance the competencies of 15 third-semester Diploma III Hospitality students in the English for Handling Complaints course at Politeknik eLBajo Commodus. Employing a qualitative case study design, data were collected from 15 students, two lecturers, and three industry partners through 16 observation sessions, semi-structured interviews, and performance assessments using an ESP-based rubric. Thematic analysis, supported by NVivo, identified patterns of improvement in language fluency, cultural sensitivity, and conflict resolution skills. Findings reveal significant enhancements in students’ confidence and professionalism in the teaching factory setting (average score 4.2/5) compared to the classroom (3.8/5), despite challenges such as limited simulation facilities. The hybrid approach effectively bridges theoretical learning and practical application, preparing students for industry demands. Recommendations include investing in simulation infrastructure, providing lecturer training, and expanding industry partnerships to optimize vocational curricula. This study contributes to the development of responsive vocational education tailored to the needs of the maritime and tourism industries. Keywords: English for Handling Complaints, teaching factory, vocational education, hospitality industry, Indonesian tourism.